Convergence Numerically of Trinomial Model in European Option Pricing - Puspita, Entit; Agustina, Fitriani; Sispiyati, Ririn (Universitas Prasetiya Mulya, 2013)
A European option is a financial contract which gives its holder a right (but not an obligation) to buy or sell an underlying asset from writer at the time of expiry for a pre-determined price. The continuous European options pricing model is given by the Black-Scholes. The discrete model can be priced using the lattice models ih here we use trinomial model. We define the error simply as the difference between the trinomial approximation and the value computed by the Black-Scholes formula. An interesting characteristic about error is how to realize convergence of trinomial model option pricing to Black-Scholes option pricing. In this case we observe the convergence of Boyle trinomial model and trinomial model that built with Cox Ross Rubenstein theory.